1990
DOI: 10.1007/bf00232858
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration from hypocotyl protoplasts of broccoli (Brassica oleracea L. ssp. italica Plenck)

Abstract: We have assessed the capacity of cultured protoplasts from two tissue sources of several commercially-grown broccoli cultivars to regenerate plants. A procedure that employs hypocotyl protoplasts and a culture medium with a high NAA:2,4-D auxin ratio was developed. The procedure permits highly efficient formation of colonies that regenerate shoots at frequencies of 8-17% with two of the four cultivars tested. The time required for the development of plants from protoplasts was 8-11 weeks. No mtDNA rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Thus, the combined and relatively high concentrations of auxins were needed to achieve optimal petal protoplast culture, suggesting that the auxins are more limiting than cytokinin for the petal protoplast proliferation. This result is consistent with earlier findings that the combined auxins were relatively effective for cell proliferation in hypocotyl protoplast cultures of Fagopyrum esculentum and Brassica oleracea (Adachi et al 1989;Kao et al 1990) and in mesophyll protoplast cultures of Felicia bergeriana and Petunia hybrida (Malaure et al 1990;Oh & Kim 1988).…”
Section: Resultssupporting
confidence: 82%
“…Thus, the combined and relatively high concentrations of auxins were needed to achieve optimal petal protoplast culture, suggesting that the auxins are more limiting than cytokinin for the petal protoplast proliferation. This result is consistent with earlier findings that the combined auxins were relatively effective for cell proliferation in hypocotyl protoplast cultures of Fagopyrum esculentum and Brassica oleracea (Adachi et al 1989;Kao et al 1990) and in mesophyll protoplast cultures of Felicia bergeriana and Petunia hybrida (Malaure et al 1990;Oh & Kim 1988).…”
Section: Resultssupporting
confidence: 82%
“…This demonstrated that the pol cytoplasm confers male sterility in broccoli, and, since one such plant possessed broccoli chloroplasts, their resuits also showed that the male sterility determinant resided on the mitochondrial genome. B. napus × B. oleracea hybrids produced by either embryo rescue following sexual crosses [ 11 ] or somatic hybridization [4] are male fertile, and male sterility was not observed in over 100 broccoli plants regenerated using the procedure employed here for the somatic hybrids [5]. Moreover, plants regenerated by our procedure from protoplast fusion products that possess a pure 2,3…”
mentioning
confidence: 86%